Creatures of the night - Pipe, Jim, 1966- (Brookfield, CT : Copper Beech Books, 1998)
Describes the unique characteristics and habits of different creatures that are active at night, including wolves, skunks, bats, and other mammals, insects, and amphibians.
Includes index.
Keywords: Nocturnal animals -- Juvenile literature; Nocturnal animals